(untitled) (Kairaranga, 2018)
Resource Teachers: Learning and Behaviour (RTLB) are receiving significantly more behaviour referrals from teachers and schools. In the cluster where I practise as an RTLB there has been a major increase in funding requests relating to concerning behaviours. Behaviourspecific requests increased from 6 percent in 2013 to 26.2 percent in 2017. Schools are now including more students who have suffered from trauma and/or neglect, who present with complex, and at times, very challenging behaviour. Some of the behaviours include the student appearing hyper-vigilant, who flies into unpredictable, uncontrollable rages, who runs away, who swears, and who verbally and even physically attacks other children or the very people who are there to support them. The usual behaviour management systems and strategies that teachers have learnt to use including rewards and consequences often have little impact on this child’s ability to remain calm, rational and therefore ready for learning (Howard 2013; Ziegler, 2015). This paper reports on an inquiry which investigated how to support children who have experienced trauma or neglect in early life, and specifically, how synthesising research in the field of childhood trauma and presenting it in a 40-minute instructional video, can support the teachers of children who present with complex and challenging behaviours due to trauma. It is essential that educators understand the physiological state these children are in, and understand the theory as well as the evidence-based practical strategies that can be used when working with traumatised students. Ultimately, by understanding these concepts, teachers will be able to support children with renewed confidence, understanding and empathy.